(untitled) (Jurnal Manajemen Perhotelan, 2012)
In hospitality industry, customer loyalty is the measurement of the success of service industry. Customer will be more satisfy when we can fulfill their need more than what he expected. It’s depended to staff’s sincerity when they give the service. Also happened at Laundry 5Asec Surabaya that point the measurement of success of services to guests from guest comment. Customer loyalty that want to be got by laundry 5Asec Surabaya can be measured by distributing quesionaires which are filled by the customer. All the questions are connected with service quality of laundry 5Asec Surabaya from customer loyalty perception. The answers will be counted to find the number of customer loyalty. By knowing the connection of service quality and customer loyalty, laundry 5Asec Surabaya can understand the customer perception to sevice quality better and make the precise strategies for improving the workmanship in the future to get customer loyalty.